Konsep Desain Website Museum Sepuluh Nopember Dalam Mengenang Peristiwa Ikonik Di Surabaya - Hidayat, Wavi; Febi Arifianto, Pungky; Aqidatun Nisa, Diana (Jurnal Sains Informatika Terapan, 2025)
Sepuluh Nopember Museum in Surabaya is a historical icon that commemorates the heroic events of November 10, 1945. However, limited access to digital information reduces the opportunity for people, especially the younger generation, to learn more about this history. This research aims to design an interface design for the Museum Sepuluh Nopember website that is informative and educational. The design method uses a design thinking approach. The results show that the user interface design to present an intuitive user experience through a clear navigation structure, the use of visual elements that support historical themes, and the integration of interactive features. Thus, this website is expected to be an effective educational media in remembering the iconic events in Surabaya while increasing public interest in the history of the nation's struggle.